2005
DOI: 10.1016/j.febslet.2005.07.037
|View full text |Cite
|
Sign up to set email alerts
|

LEAFY COTYLEDON 2 activation is sufficient to trigger the accumulation of oil and seed specific mRNAs in Arabidopsis leaves

Abstract: LEAFY COTYLEDON 2 (LEC2) is a key regulator of seed maturation in Arabidopsis. To unravel some of its complex pleiotropic functions, analyses were performed with transgenic plants expressing an inducible LEC2:GR protein. The chimeric protein is functional and can complement lec2 mutation. Interestingly, the induction of LEC2 leads to the accumulation of storage oil in leaves. In addition, short-term induction and use of translation inhibitors allowed to demonstrate that LEC2 can directly trigger the accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
95
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(103 citation statements)
references
References 27 publications
8
95
0
Order By: Relevance
“…3D). These results are consistent with other studies that have shown that ectopic-expressing LEC genes promote somatic embryo development and that, particularly for 35S::LEC1, seedlings arrest as embryo-like seedlings and fail to develop further (Lotan et al, 1998;Stone et al, 2001Stone et al, , 2008Santos-Mendoza et al, 2005). Here, we show that contrary to nontransformed leaf embryos, functional KdLEC1 expression under the control of LEC1 promoter and terminator in K. daigremontiana resulted in dormant seed-like leaf embryos.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…3D). These results are consistent with other studies that have shown that ectopic-expressing LEC genes promote somatic embryo development and that, particularly for 35S::LEC1, seedlings arrest as embryo-like seedlings and fail to develop further (Lotan et al, 1998;Stone et al, 2001Stone et al, , 2008Santos-Mendoza et al, 2005). Here, we show that contrary to nontransformed leaf embryos, functional KdLEC1 expression under the control of LEC1 promoter and terminator in K. daigremontiana resulted in dormant seed-like leaf embryos.…”
Section: Discussionsupporting
confidence: 82%
“…Together, these results show that the functional KdLEC1 transgene is expressed in all the transgenic plant leaf margins analyzed and indicate that the phenotypes observed on plantlet development of the transgenic plants are due to the expression of the functional KdLEC1 gene under the regulation of LEC1 promoter and terminator. These results are consistent with other analysis showing that ectopic expression of LEC1, FUSCA3 (FUS3), and LEC2 genes induces the accumulation of lipid and protein reserves characteristic of developing seeds in cells of vegetative and reproductive tissues (Lotan et al, 1998;Stone et al, 2001Stone et al, , 2008Santos-Mendoza et al, 2005). Moreover, seed-specific overexpression of maize (Zea mays) LEC1 (ZmLEC1) resulted in an average 35% increase in seed oil but reduced germination and vegetative growth in the field (Shen et al, 2010) In Arabidopsis, the seed maturation program is controlled by a network of transcription factors that includes the B3 domain transcription factors (ABA-INSENSITIVE3 [ABI3], FUS3, and LEC2; Giraudat et al, 1992;Luerssen et al, 1998;Stone et al, 2001) and two LEC1-type HAP3 family CCAAT-binding factors, LEC1 and L1L (Lotan et al, 1998;Kwong et al, 2003).…”
Section: Discussionsupporting
confidence: 81%
“…ABI3 and FUS3 expression occurs later in embryogenesis and their overexpression results in ectopic expression of some seed maturation genes, such as At2S3 and CRC, in vegetative tissues in an ABA-dependent manner, demonstrating that the SSP gene expression is controlled by LEC1 through the regulation of ABI3 and FUS3 Kagaya et al, 2005b). Genetic and molecular studies have shown that ABI3, FUS3 and LEC2 regulate oleosin gene expression and lipid accumulation (Crowe et al, 2000;Santos-Mendoza et al, 2005;Baud et al, 2007). Loss of ABI3 function alters accumulation of seed storage reserves and leads to loss of desiccation tolerance, dormancy, ABA sensitivity upon germination and chlorophyll degradation (Vicente-Carbajosa & Carbonero, 2005).…”
Section: A Regulatory Network For Seed Maturationmentioning
confidence: 99%
“…ASIL1 expression also exhibited a modest response to auxin and the level of ASIL1 transcript is elevated at 1h post-imbibition, therefore the rise in ASIL1 transcript levels may correspond to the distribution of auxin in cells of germinating seeds (Gao et al, 2009). LEC1 and LEC2 function upstream of other embryonic and seed maturation genes and their ectopic expression is sufficient to provoke the embryonic program in vegetative tissues (Lotan et al, 1998;Stone et al, 2001;Santos-Mendoza et al, 2005). Therefore, expression of these two major regulators of embryonic programming should be strictly prevented during germination and seedling development.…”
Section: Wwwintechopencommentioning
confidence: 99%
See 1 more Smart Citation